Катамнез больных детским церебральным параличом города Северска; Медицинский Вестник Юга России; № 3 - Рогов А. В.; Левицкий Е. Ф.; Барабаш Р. З.; Коршунов С. Д.; Дорошева Т. Г.; Нечаева Е. И.; Пашков В. К. Вячеслав Константинович (2014, 2014)
Заглавие с экрана